2020
DOI: 10.1111/exsy.12501
|View full text |Cite
|
Sign up to set email alerts
|

Artificial plant optimization algorithm to detect infected leaves using machine learning

Abstract: Plant leaves play an important role in the diagnosis of plant diseases. Losses from such diseases can have a significant economic as well as environmental impact. Thus, examination of leaves into a healthy or infected carries substantial importance. An improved artificial plant optimization (IAPO) algorithm using machine learning has been introduced that identifies the plant diseases and categorize the leaves into healthy and infected on a private dataset of 236 images. Features are extracted from the images u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 19 publications
(20 reference statements)
2
12
0
Order By: Relevance
“…In (11), a white blood cell classification model based on the nature-inspired approach is developed, and when a comparison analysis with other existing nature-inspired algorithms is done, it was found that the proposed model was extremely fast and precise in the analysis of hematological issues. An efficient machine-learning framework to identify and classify leaves has been proposed in (12). Later, the proposed model was compared with some classifiers like random forest and KNN algorithm.…”
Section: Related Workmentioning
confidence: 99%
“…In (11), a white blood cell classification model based on the nature-inspired approach is developed, and when a comparison analysis with other existing nature-inspired algorithms is done, it was found that the proposed model was extremely fast and precise in the analysis of hematological issues. An efficient machine-learning framework to identify and classify leaves has been proposed in (12). Later, the proposed model was compared with some classifiers like random forest and KNN algorithm.…”
Section: Related Workmentioning
confidence: 99%
“…Another application was given by Deepak Gupta et al [14] on an artificial plant optimization algorithm to detect infected leaves using machine learning and in [15] where he presented a novel approach on seasonal Crops Disease Prediction and Classification using Deep Convolutional Encoder Network. Neural network and it applications are vast as demonstrated by Gupta et al in [16], [17], and [18].…”
Section: Related Workmentioning
confidence: 99%
“…Hi et al [37] noted that the incorporation of the algorithms helped to reduce the cost of the calculations, improved the accuracy of the measurements, and minimized the local minimum problem; this was evident in the optimization of the grid integrated renewable energy [39], intelligent allocation of water resources in multi-reservoir systems [40], optimization of the agricultural machinery path planning [41,42], and detection of disease infestation in plant leaves [43,44]. The suitability of all BIAs in optimizing IoT systems in agriculture is constrained by the complexity and uncertainty of ubiquitous IoT services.…”
Section: Introductionmentioning
confidence: 99%